2017
DOI: 10.3390/su9040641
|View full text |Cite
|
Sign up to set email alerts
|

Household Perceptions about the Impacts of Climate Change on Food Security in the Mountainous Region of Nepal

Abstract: Abstract:This study tried to understand the mountainous households' perception of climate change and its impacts on food security in the Lamjung district of Nepal. The study attempted to find out changes in households food security and daily activities in the face of climate change for the last twenty years. The study started with the 150 household surveys along with participatory rural appraisal to understand the climate change perception of local people and its impact on dimensions of food security. Househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Similar adaptation measures have been known to practise at farm-level in a recent study by Kabir et al (2017). Changes in cultivation practices such as water conservation methods, changes in sowing time and introduction of cash crops have already been reported (Poudel et al, 2017). In this study, the adaptation in agriculture are mainly autonomous and it implies that individuals or communities undertaking adaptation to climatic risk to agriculture independently of outside intervention.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar adaptation measures have been known to practise at farm-level in a recent study by Kabir et al (2017). Changes in cultivation practices such as water conservation methods, changes in sowing time and introduction of cash crops have already been reported (Poudel et al, 2017). In this study, the adaptation in agriculture are mainly autonomous and it implies that individuals or communities undertaking adaptation to climatic risk to agriculture independently of outside intervention.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, farmers have reported the incidences of drought for declining yield for specified years. The declining crop production will have severe impact on overall food security (Poudel et al, 2017). Studies in South Asian context also reported significant negative impacts on crop productivity and food supply due to extreme events, especially floods and droughts (Chhetri et al, 2012;Bandara & Cai, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for mountain areas, where local climate data are sparse (Xu and Grumbine 2014) and climate change poses a significant threat to rural livelihoods. Rural populations depend on locally accessible natural resources for their livelihoods; however, they are often not considered in decision-making due to, for example, isolation, inaccessibility, and relative poverty (UNEP 2016;Poudel et al 2017). Despite several studies on issues such as perceptions of climate change, adaptation, and policy implications undertaken in Asia (Ingty 2017; Barrett and Bosack 2018), Africa (Hameso 2017; Mkonda and He 2017), and Latin America (Postigo et al 2012; Vidaurre de Mulczyk 2016; L opez et al 2017; Weber-Alvarez 2017; Paerregaard 2018), there is still little evidence of the value added by integrative approaches in mountain areas (McDowell and Koppes 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They believe that this effect will further increase climate vulnerability in the future. However, the local populations have practiced some local climate change adaptation measures using their indigenous knowledge, such as growing improved crop varieties, improved irrigation systems and fertilizers as coping strategies [6].…”
Section: Introduction mentioning
confidence: 99%